Analisis Sistem Informasi Raport Digital Madrasah (RDM) pada Madrasah Ibtidaiyah Negeri (MIN) 9 Kota Banda Aceh - Khuzari, M.; Akbar, Rizaldi; Junaidi, Rahmat (Jurnal Sistem Komputer (SISKOM), 2025)
This study aims to analyze the digital report card information system (RDM) in terms of user satisfaction using the End User Computing Satisfaction (EUCS) method at Madrasah Ibtidaiyah Negeri (MIN) 9 Banda Aceh. In the digital era, the digital report card information system has become a crucial tool in supporting administrative processes and assessments in the education sector, particularly in madrasahs. This study was conducted to understand to what extent the implementation of RDM can meet the needs and expectations of users, including teachers, students, and other stakeholders at MIN 9 Banda Aceh. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to users of the RDM system at MIN 9 Banda Aceh. User satisfaction was measured based on five EUCS dimensions: content, accuracy, format, ease of use, and timeliness. The results of the study indicate that, overall, users are satisfied with the RDM system in use. The ease of use and timeliness dimensions received the highest ratings, indicating that users find the system easy to use and that it provides timely information. However, there are several aspects within the content and accuracy dimensions that need improvement to enhance overall user satisfaction. This study provides important insights into the effectiveness of digital report card information systems in madrasah settings. The findings are expected to offer valuable input for system developers and madrasah administrators to improve the quality of services and functionality of RDM, thus better meeting the needs of users and supporting a more efficient educational process.